Distribution and extirpation of pigs in Pacific Islands: a case study from Palau. Issue 3 (10th June 2013) - Clark, Geoffrey; Petchey, Fiona; Hawkins, Stuart; Reepmeyer, Christian; Smith, Ian; Masse, W. Bruce
Abstract Neolithic arrival in the Pacific involved, as in other parts of the world, the translocation of domesticated plants and animals by pottery‐making cultures in prehistory. Globally uncommon, though, was the abandonment of pottery on some islands and the extirpation of the pig (Sus scrofa/verrucosus) and dog (Canis familiaris) – the two largest mammalian quadrupeds introduced to Oceania – from the subsistence and cultural systems. This paper examines the extirpation of pigs from the Palau Islands as a case study to understand why an important domesticate has such an uneven prehistoric distribution. When suids are fed agricultural produce required to sustain the human population, it has been proposed that competition and extirpation will result, especially on small islands with limited arable land. However, pigs are considered problem animals in many environments because of the damage they cause to horticultural production, particularly the effects of free‐range pigs on gardens and plantations. It is suggested that extirpation and low‐level animal keeping are a response to the threat that pigs pose to plant food yields and social relations.